2009
DOI: 10.1243/09544054jem1563
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of surface generation in the ultraprecision polishing of freeform surfaces

Abstract: The use of freeform designs in engineering surfaces has become increasingly popular over the last decade. Applications of freeform shapes range from aesthetics of components to the bending of light rays through advanced optic designs. The fabrication of the components for these applications requires submicrometre form accuracy, in some cases with surface roughness at nanometric levels. Ultraprecision polishing is an emerging technology for the fabrication of high-precision and high-quality freeform surfaces. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Machining bioimplants by means of grinding processes followed by polishing is a favourable solution for removing the remained damages. Figure 8 shows the surface quality with and without a finishing process of polishing [123]. It was reported that a smoother surface exhibited a better corrosion resistance, and hence prolonged the lifetime of the implant.…”
Section: Polishingmentioning
confidence: 99%
See 3 more Smart Citations
“…Machining bioimplants by means of grinding processes followed by polishing is a favourable solution for removing the remained damages. Figure 8 shows the surface quality with and without a finishing process of polishing [123]. It was reported that a smoother surface exhibited a better corrosion resistance, and hence prolonged the lifetime of the implant.…”
Section: Polishingmentioning
confidence: 99%
“…It was reported that a smoother surface exhibited a better corrosion resistance, and hence prolonged the lifetime of the implant. In addition, the conformity between the coupling joints would reduce the friction coefficient, which was very attractive with respect to the bearing orthopaedic implants [123,124]. Conventional polishing methods include free abrasive polishing, fixed abrasive polishing, belt polishing, etc., which have all been comprehensively investigated in the past decades.…”
Section: Polishingmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional methods of fabricating glass lenses are grinding, polishing and lapping [22][23][24][25], dating back to the 1500s when microscopes [26,27] and telescopes [28][29][30] were invented. However, lens polishing skills were among talented craftsmen [26,28], developed from their life-long experience.…”
Section: Introductionmentioning
confidence: 99%